Perceptions about hearing aids from elderly non-users: a bicultural point of view (Italy and USA) - B. Alvarado (Audiology Research, 2011)
Perceptions about hearing aids can vary across people of different cultural backgrounds depending upon beliefs, healthcare policies, education, etc. This study investigated the perceptions about hearing aids of non-user elderly subjects from Italy (IT) and the United States (US) who complained of hearing loss with regard to: benefit of hearing aids, cosmetic appearance of hearing aids, cost of hearing aids, social pressure about the use of hearing aids, and about the primary provider for hearing aid services. A 15-item survey called ‘Perceptions about hearing aids from non-users’ (PHANU) was developed and administered to 184 subjects in IT and 160 subjects in the US. The subjects consisted of a random sample of ≥60 year-old non-users of hearing aids who reported difficulty hearing. There were two subject groups in each country: a clinical ITC/USC and a non-clinical ITNC/USNC. The PHANU survey items were analyzed using the Rasch rating scale. Significant differences were observed for survey questions pertaining to social pressure, cost, and benefit between the USC and USNC groups. The ITC and ITNC groups demonstrated significant differences with regard to cosmetic and benefit questions. Significant differences with regard to social pressure aspects were observed between the USC and ITC groups. The USNC and ITNC groups showed significant differences with regard to benefit and cost. Audiologists were the predominant hearing aid provider in both US groups. Otolaryngologists were preferred in both IT groups. The USNC group had the most positive perceptions about hearing aids. The PHANU survey revealed that subjects from IT and the US can have contrasting opinions about hearing aids. The PHANU survey demonstrated good validity and reliability. Due to the survey’s experimental design, test-retest reliability indexes could not be obtained. PHANU shows promise as a tool that can benefit the hearing-impaired, professionals, industry, and healthcare policy makers.